Karakterisasi Tanah Diatom dan Aplikasinya Pada Industri Minyak Goreng - Lisma Luciana Lisma Luciana (Fakultas Teknik, 2017)
Research on the activation of diatomaceous earth bleachingand its application in the cooking oil industry was made by modifying natural diatomaceous earth with four methods of activation. Activation method 1 and 2 are added with H2SO4 and H2O2 and then heated to 100°C for one hour to method 1, while formethod 2 of diatomaceous earth sample is heated to temperatures reaching 550°C for two hours. On activation method 3 and 4 with the addition of NaOH solution and MnCL2 with 100°C combustion for sample method 3 and 550°C for method 4, which only differentiate the length of combustion time. Reduction in the amount of dye in the cooking oil was done by varying the weight of the absorbent 2.5, 5, 7.5, and 10g and 100°C adsorption temperature, 110°C, 120°C and 130°C. In this research, characterization of adsorbent consisting of natural diatomaceous earth and modified diatomaceous earth. Characterization was done by using instruments Scanning Electron Microscope (SEM-EDAX), X-ray diffraction (XRD), Fourier Transform Infrared (FTIR) and X-Ray Fluorescence (XRF)